COMPARISON OF THE PROPERTIES OF INDUSTRIAL /7-GALACTOSIDASE FOR LACTOSE HYDROLASE IN DAIRY RAW MATERIALS - Anastasiya Karaseva; Irina Kylikova; Georgy Anisimov; Gennady Slyusarev (Вестник Северо-Кавказского федерального университета)
The main characteristics of ß-galactosidase enzyme, various basic methods of enzyme preparation are considered in the article. A comparative evaluation of the ß-galactosidase enzyme producers was carried out. Preparations of ß-galactosidase make it possible to provide a portion of the population suffering from lactase deficiency, dairy products almost free of lactose. Processing the milk with the enzyme when concentrating, especially when it is stored at low temperatures, improves stability during regeneration